IMPROVING SATISFACTION WITH SERVICE QUALITY OF WOMEN’S CAREER DEVELOPMENT ENTERPRISES EUA ATHON COMMUNITY, BANG PHUT SUBDISTRICT, PAK KRET DISTRICT, NONTHABURI PROVINCE - Thoucharee, Sedthapoom (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
This research aims to (1) study the problem of satisfaction with the customer service quality of Women's Career Development Enterprises and (2) improve satisfaction on customer service quality of women's career development enterprises. It measures the satisfaction of 20 customers in 5 aspects: the concrete aspect of the service, reliability (trust in the service), consumer response, providing confidence to service recipients, and sympathy for service recipients. After that, training, follow-up, data collection, and analysis of paired samples T-Test followed. The results showed that the mean level of satisfaction with service quality between before and after training was higher in 4 aspects: reliability (trust in service), consumer response, providing confidence to service recipients, and sympathy for service recipients. The mean difference was significant at = 0.05, but in the concrete aspect of the service, there was no significant difference in mean at = 0.05.